Towards fifth generation universities of medical sciences - Ali Mohammad Mosadeghrad; Parvaneh Isfahani (Payesh)
Dear Editor, The university is the driving force of science, research and technology and plays a key role in the political, economic, social, cultural and technological development of a country. Universities underwent changes throughout history due to political, economic, social and environmental changes. The course of transformation of universities shows five different generations, including the first generation (education-oriented university), the second generation (research-oriented university), the third generation (Innovation-oriented university), the fourth generation (Society-oriented university) and the fifth generation (Value-oriented University). Most of Iran's medical universities are second generation universities. The transformation of Iran's medical universities into fourth and fifth generation universities requires the commitment and efforts of all their members and the creation of fundamental changes in the structure, culture, tasks and processes of the university. The mission and vision of universities should be redefined according to the emerging challenges of society and the needs of its various stakeholders.